An nLCA approach to support consumer meal decisions: a New Zealand case study of toppings on toast - Majumdar, Shreyasi; McLaren, Sarah J.; van der Pols, Jolieke C.; Lister, Carolyn E. (Frontiers in Sustainable Food Systems, 2024)
This study investigates the development and potential application of a nutritional Life Cycle Assessment (nLCA) method to rank meals, using a case study of a 'toppings on toast' (ToTs) meal. Methodological issues are investigated in the context of application to support consumers to make more informed food choices at the meal level. performing toppings in the ToT meal context. However, the results also showed that water-soluble vitamins and unsaturated fats included in the NRF28.3 index contributed significantly to the nutritional scores for most of the toppings and were instrumental in the rank changes for the toppings which are particularly rich in these nutrients. Thus, for a more diverse range of toppings/meals, an expanded index including these nutrients can generate more nuanced rankings.This study contributes to the nascent but fast-growing nLCA research field, particularly within the meal context. The method used in this case study could be applied in food composition databases, restaurant menus, and websites/apps that provides recipes for meals. However, the study also highlighted the potentially significant variability in climate change and nutritional values in the toppings associated with different production practices, seasonality, and different varieties of the same product. Any future development of nLCA-based meal level rankings should address this variability and communicate it to the consumer.